Biodiesel synthesis from Ceiba pentandra oil by microwave irradiation-assisted transesterification: ELM modeling and optimization. (February 2020) - Silitonga, A.S.; Shamsuddin, A.H.; Mahlia, T.M.I.; Milano, Jassinne; Kusumo, F.; Siswantoro, Joko; Dharma, S.; Sebayang, A.H.; Masjuki, H.H.; Ong, Hwai Chyuan
Abstract: In this study, microwave irradiation-assisted transesterification was used to produce Ceiba pentandra biodiesel, which accelerates the rate of reaction and temperature within a shorter period. The improvement of biodiesel production requires a reliable model that accurately reflects the effects of input variables on output variables. In this study, an extreme learning machine integrated with cuckoo search algorithm was developed to predict and optimize the process parameters. This model will be useful for virtual experimentations in order to enhance biodiesel research and development. The optimum parameters of the microwave irradiation-assisted transesterification process conditions were obtained as follows: (1) methanol/oil ratio: 60%, (2) potassium hydroxide catalyst concentration: 0.84%(w/w), (3) stirring speed: 800 rpm, and (4) reaction time: 388 s. The corresponding Ceiba pentandra biodiesel yield was 96.19%. Three independent experiments were conducted using the optimum process parameters and the average biodiesel yield was found to be 95.42%. In conclusion, microwave irradiation-assisted transesterification is an effective method for biodiesel production because it is more energy-efficient, which will reduce the overall cost of biodiesel production. Graphical abstract: Image 1 Highlights: Ceiba pentandra biodiesel is produced using a microwave reactor. ELM with cuckoo search algorithm is used to optimize the process parameters. There is good agreement between the predicted and test optimum biodiesel yield. The ELM-CS model facilitates the prediction and optimum process parameters.